Enhancing ESL rural students’ speaking skills through multimedia technology-assisted project-based learning: Conceptual paper - Kennedy Yamil; Noraini Said; Suyansah Swanto; Wardatul Akmam Din (Global Academic Excellence (M) Sdn Bhd, 2022)
The recent Covid-19 pandemic has changed and impacted the country's education landscape, a paradigm shift from face-to-face teaching and learning style into home-based learning and teaching (PdPR). During the period, teachers had come out with various teaching strategies to assess pupils’ and some of these strategies are still relevant in this current post pandemic education. Speaking skills in the Malaysian Primary ESL classroom are five elements assessed in the Classroom-Based Assessment (CBA). The CBA achievement of a class in a rural school in Kudat, Sabah, showed that most students performed poorly in speaking skills. Based on the teacher's perspective as a researcher, the problem occurred due to the English Language's lack of exposure and usage. It is only spoken during an English class and not practised outside schooling hours. In this paper, the researcher aims to provide a literature review and past studies on enhancing primary ESL students' speaking skills through multimedia technology-assisted project-based learning. After investigating how multimedia technology-assisted project-based learning could improve the students' speaking skills from the literature review, the researcher proposes this study be carried out at a rural government school in Kudat, Sabah. This research aims to investigate students' speaking performance after the implementation of multimedia technology-assisted project-based learning.